2023
DOI: 10.1093/jamia/ocad223
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacy in undergraduate pharmacy education: a scoping review

Mashael Alowais,
Georgina Rudd,
Victoria Besa
et al.

Abstract: Objectives Conduct a scoping review to identify the approaches used to integrate digital literacy into undergraduate pharmacy programs across different countries, focusing on methods for education, training, and assessment. Materials and methods Following the Joanna Briggs Institute methodology, we searched 5 electronic databases in June 2022: MEDLINE (Ovid), PubMed, Embase, Scopus, and CINAHL. Three independent reviewers scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 64 publications
(204 reference statements)
0
2
0
Order By: Relevance
“…Increasing adoption of digital health interventions in pharmacy practice requires a digitally literate pharmacy workforce. 17 However, the International Pharmaceutical Federation indicated in its global survey on “digital health in pharmacy education” that very few pharmacy schools have integrated digital health education into their curricula. 13 The existing educational approaches included theoretical and experiential learning as well as simulations involving digital technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing adoption of digital health interventions in pharmacy practice requires a digitally literate pharmacy workforce. 17 However, the International Pharmaceutical Federation indicated in its global survey on “digital health in pharmacy education” that very few pharmacy schools have integrated digital health education into their curricula. 13 The existing educational approaches included theoretical and experiential learning as well as simulations involving digital technologies.…”
Section: Discussionmentioning
confidence: 99%
“…13 The existing educational approaches included theoretical and experiential learning as well as simulations involving digital technologies. 17 The design of our practical elective course allowed pharmacy students to get theoretical insights into wearable technology as well as novel experiential learning involving the effect of food, physical activity, and stress on physiological parameters. Thus, the results of the elective practical course confirm previous studies which demonstrated that the experience of wearing digital devices and interpreting health-related data enhance engagement and learning among medical, dental, and pharmacy students, as well as practicing pharmacists.…”
Section: Discussionmentioning
confidence: 99%